Systematic Literature Review: The Role of Audit Quality in Detecting Fraud - Jenny Liana; Rita Friyani; Mukhzarudfa Mukhzarudfa (Green Publisher Indonesia, 2026)
This research aims to examine articles related to the role of audit quality in detecting fraud. This study uses the blibliometrics-based Systematic Literature Review (SLR) method to identify, evaluate, and synthesize relevant empirical research results from Scopus' reputable database. The literature search was carried out with a combination of the keywords fraud detection and quality audit. Of the 110 articles identified, as many as 34 articles met the inclusion criteria after going through the selection process using the PRISMA protocol. The results of this study show that fraud detection is a multidimensional phenomenon influenced by a combination of individual auditor factors (competence, professionalism, skepticism), quality of internal governance and control, and the use of technologies such as CAATs, big data analytics, and artificial intelligence. Audit quality has proven to be an important catalyst that strengthens the effectiveness of fraud detection, although traditional proxies such as KAP size and tenure audits do not always consistently explain fraud detection capabilities. Overall, these findings confirm that synergies between audit quality, governance mechanisms, and intelligent automation are needed to improve the effectiveness of fraud prevention and detection.